(untitled) (Música Hodie, 2024)
The mastery of performing musical pieces using wind instruments depends on the musician’s level of preparation. The objective of this article is to investigate the influence of the teaching approach employed in wind instrument instruction on the improvement of musical technique. The study was based on the recruitment of control (Group 1) and experimental (Group 2) groups. Group 1 was taught using traditional methods, while Group 2 was taught using an updated methodology incorporating an individualized approach to instruction and the use of the Virtual Trumpet digital application. It was determined that students in the experimental group were able to achieve higher trumpet playing scores, primarily attributed to breathing technique and embouchure (p≤0.05). Additionally, students in Group 2 exhibited higher endurance scores (the highest scores) compared to students in Group 1 (scores ranging from 3 to 5), attributed to the carefully designed individualized teaching approach. It was found that the overall quality of performance among students in Group 2 corresponded to grades of 4 and 5. The practical significance of this study lies in the potential for improving trumpet instruction methods by tailoring them to individual musicians’ capabilities.